The Risk of Financial Bubbles in Renewable Energy Markets - Ignas Mikalauskas; Darius Karaša (Energies)
Policy incentives and technological advancements are driving the rapid expansion of renewable energy industries. However, as speculative investment intensifies, concerns about the potential formation of financial bubbles are growing. This paper examines financial saturation in renewable energy markets, emphasizing key bifurcation and overheating thresholds that indicate speculative risks. Using a financial saturation model, the study evaluates market overheating across three major renewable energy sectors—solar PV, wind energy, and battery storage—based on a scenario analysis from Bloomberg’s New Energy Outlook (NEO) 2024. The findings reveal that battery storage is the most susceptible to speculative investment, with bifurcation (~70% market saturation) projected by 2031 (medium term) and by 2038 (long term) under the Net-Zero Scenario (NZS), and by 2042 under the Economic Transition Scenario (ETS). In the long term, financial overheating (~90% market saturation) in battery storage is projected by 2048 under the ETS. Solar PV also faces speculative risks, with bifurcation expected by 2030 (ETS, medium term), 2039 (ETS, long term), and 2041 (NZS, long term). Overheating in the solar sector is projected by 2048 (ETS, long term) and 2050 (NZS, long term). Wind energy exhibits a more gradual saturation pattern, with bifurcation expected by 2031 (ETS, medium term), 2038 (ETS, long term), and 2045 (NZS, long term), while overheating is anticipated by 2049 (ETS, long term). These findings highlight the need for regulatory oversight to mitigate speculative investment risks. To enhance financial stability, policy recommendations include gradual subsidy phase-outs, financial stress testing, and diversified investment strategies. Maintaining a stable investment environment is essential for long-term climate goals and energy security.